2019
DOI: 10.12688/wellcomeopenres.15059.1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid transcriptional responses to serum exposure are associated with sensitivity and resistance to antibody-mediated complement killing in invasive Salmonella Typhimurium ST313

Abstract: Background: Salmonella Typhimurium ST313 exhibits signatures of adaptation to invasive human infection, including higher resistance to humoral immune responses than gastrointestinal isolates. Full resistance to antibody-mediated complement killing (serum resistance) among nontyphoidal Salmonellae is uncommon, but selection of highly resistant strains could compromise vaccine-induced antibody immunity. Here, we address the hypothesis that serum resistance is due to a distinct genotype or transcriptome response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…This indicates that significant phenotypic variation can occur within highly clonal microbial populations. Similar data has been reported for other bacteria, including Salmonella enterica serovar Typhimurium 34 . However, the binding phenotypes correlated with both differences in phagocytosis and serum sensitivity, signifying the importance of having high-throughput methods to phenotypically screen large populations of isolates as genomic data alone cannot not always be predictive of a phenotype.…”
Section: Discussionsupporting
confidence: 88%
“…This indicates that significant phenotypic variation can occur within highly clonal microbial populations. Similar data has been reported for other bacteria, including Salmonella enterica serovar Typhimurium 34 . However, the binding phenotypes correlated with both differences in phagocytosis and serum sensitivity, signifying the importance of having high-throughput methods to phenotypically screen large populations of isolates as genomic data alone cannot not always be predictive of a phenotype.…”
Section: Discussionsupporting
confidence: 88%
“…Other reports have shown that anti-LPS antibodies stimulate low complement-dependent killing against S. Enteritidis human blood isolates [ 51 ]. Furthermore, S. Typhimurium ST313, which dominates in sub-Saharan Africa, is highly serum resistant and expresses distinct transcriptional patterns that may aid in escaping this killing mechanism [ 52 ]. It is a good future research direction to illustrate how they escape this complement-dependent killing mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…GMMAs are attractive vaccine candidates because they are comprised of multiple antigens that can stimulate an immune response [ 65 ]. Several studies have focused on developing GMMAs purified from bacteria with different genetic modifications as vaccine candidates for NTS [ 29 ].…”
Section: Discussionmentioning
confidence: 99%